Hereditary Spherocytosis in a 22 Month Old Child - Sultana, Mst Musarrat; Islam, Md Shafiqul; Mia, Md Sanaul Haque (TAJ: Journal of Teachers Association, 2018)
Hereditary spherocytosis (HS) is a familial hemolytic disorder with marked heterogeneity of clinical features, ranging from asymptomatic condition to a fulminant hemolytic anemia. Although a positive family history of spherocytosis increases the risk for this disorder, it may be sporadic in some case. A 22-month old girl was admitted in Rajshahi Medical College Hospital with pallor and jaundice. Her parents gave history of repeated episodes of pallor and jaundice since 8 month of age with negative family history. Blood film showed plenty of spherocytes, reticulocytosis of 15.0%, negative direct antiglobulin test& positive osmotic fragility test. She was managed conservatively on nutritional supplements& one unit of blood transfusion. To the best of our knowledge, this is the first reported case of hereditary spherocytosis from Rajshahi Medical College Hospital. TAJ 2017; 30(2): 79-82